TINJAUAN MAQASID SYARI’AH TERHADAP OBLIGASI SYARIAH (SUKUK) - Alvien Septian Haerisma (IAIN Syekh Nurjati Cirebon, 2017)
Abstract One of the instruments offered in the capital market, namely sharia bonds (sukuk). This has become a major attraction for both corporations and governments. With the acquisition of funds through the issuance of sukuk, corporations and the government means that there will be large funds available so as to increase the financing of sharia financial institutions. The need for companies or governments to build the infrastructure and expansion of private companies, this becomes one of the options in realizing alternative funding sources for the company and economic progress nationally. These five needs are aimed at fulfilling the following objectives: (1) Dharuriyah, which is the mandatory requirement to fulfill the needs of the world and the hereafter, (2) Hajj is the need which alleviates the burden of the masyaqah (difficulties) of every human being, (3) Tahsinat, complementary needs. The purpose of this study, trying to outline the benefits of the issuance of sukuk country to the nation and state of Indonesia, also see how the view of maqasid syariah about the benefits of Islamic bonds (sukuk). Keywords: Syariah Bond, Maqasid Syariah, Capital Market Instruments. Abstrak Salah satu instrumen yang ditawarkan di pasar modal, yaitu obligasi syariah (sukuk). Hal ini telah menjadi daya tarik utama bagi korporasi maupun pemerintah. Dengan diperolehnya dana melalui penerbitan sukuk, korporasi maupun pemerintah berarti akan tersedia dana yang besar sehingga dapat meningkatkan pembiayaan lembaga keuangan syariah. Kebutuhan perusahaan atau pemerintah guna membangun infrastruktur dan ekspansi perusahaan swasta, hal ini menjadi salah satu pilihan dalam mewujudkan sumber dana alternatif bagi perusahaan dan kemajuan ekonomi secara nasional. Kelima kebutuhan ini bertujuan memenuhi tujuan-tujuan berikut, yaitu: (1) Dharuriyah, yaitu kebutuhan wajib agar terpenuhinya kebutuhan dunia dan akhirat, (2) Hajiyat, yakni kebutuhan yang meringankan beban masyaqah (kesulitan) setiap manusia, (3) Tahsinat, ialah kebutuhan pelengkap. Tujuan dari penelitian ini, mencoba menjabarkan manfaat atas penerbitan sukuk negara bagi bangsa dan negara Indonesia, juga melihat bagaimana pandangan maqasid syariah tentang manfaat obligasi syariah (sukuk). Kata Kunci: Obligasi Syariah, Maqasid Syari’ah, Instrument Pasar Modal.